Convection-enhanced Delivery of Therapeutics for Malignant Gliomas - SAITO, Ryuta (Neurol Med Chir (Tokyo), 2017)
Convection-enhanced delivery (CED) circumvents the blood–brain barrier by delivering agents directly into the tumor and surrounding parenchyma. CED can achieve large volumes of distribution by continuous positive-pressure infusion. Although promising as an effective drug delivery method in concept, the administration of therapeutic agents via CED is not without challenges. Limitations of distribution remain a problem in large brains, such as those of humans. Accurate and consistent delivery of an agent is another challenge associated with CED. Similar to the difficulties caused by immunosuppressive environments associated with gliomas, there are several mechanisms that make effective local drug distribution difficult in malignant gliomas. In this review, methods for local drug application targeting gliomas are discussed with special emphasis on CED. Although early clinical trials have failed to demonstrate the efficacy of CED against gliomas, CED potentially can be a platform for translating the molecular understanding of glioblastomas achieved in the laboratory into effective clinical treatments. Several clinical studies using CED of chemotherapeutic agents are ongoing. Successful delivery of effective agents should prove the efficacy of CED in the near future.